Strategi Komunikasi Hubungan Masyarakat Youth Ranger Indonesia dalam Penyebaran Informasi - Suryana, Syifa Rachmania; Santoso, Hudi; Saleh, Amiruddin; Pranata, Rici Tri Harpin; Manisya, Nabila; Maharani, Khalila Zahra (DAS Institute, 2024)
The development of information technology has presented challenges for non-profit organizations such as Youth Ranger Indonesia (YRI) in information dissemination activities, especially for its target audience, namely youth. As an organization that focuses on youth empowerment, YRI requires an effective communication strategy to reach the audience and ensure that the message delivered can be received properly and correctly. This study aims to determine the media and communication strategies used by YRI Public Relations (PR). This study uses a qualitative descriptive approach, with primary data obtained from in-depth interviews with YRI PR, while secondary data is obtained from literature and YRI social media documentation. The communication strategy described refers to the 4 Step of Public Relations (RACE) theory, namely research, action, communication and evaluation from Cutlip, Center and Broom. The results of the study show that YRI uses digital media such as WhatsApp, Gmail and Instagram. The communication strategy used by YRI is in accordance with the RACE theory, and has been proven to help YRI PR carry out information dissemination activities more effectively. This research is expected to be a reference for YRI Public Relations in developing more effective information dissemination strategies, to strengthen YRI's role in efforts to increase youth potential.